2013
DOI: 10.1371/journal.pone.0080157
|View full text |Cite
|
Sign up to set email alerts
|

Maraviroc as Intensification Strategy in HIV-1 Positive Patients with Deficient Immunological Response: an Italian Randomized Clinical Trial

Abstract: BackgroundImmunological non-responders (INRs) lacked CD4 increase despite HIV-viremia suppression on HAART and had an increased risk of disease progression. We assessed immune reconstitution profile upon intensification with maraviroc in INRs.MethodsWe designed a multi-centric, randomized, parallel, open label, phase 4 superiority trial. We enrolled 97 patients on HAART with CD4+<200/µL and/or CD4+ recovery ≤25% and HIV-RNA<50 cp/mL. Patients were randomized 1:1 to HAART+maraviroc or continued HAART. CD4+ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
(22 reference statements)
1
26
0
1
Order By: Relevance
“…The compound has been associated with some immunological benefits such as a higher CD4 increase and, although less than expected, reduced immune activation in patients with poor immunological recovery. [186] The drug, used in combination with other ARVs, has been proven to be effective in blocking HIV entry both in naïve and in experienced patients. The CNS target cells are usually expressing the CCR5 and most of the viruses are R5 tropic in the CSF (even if patients harbour X4-tropic viruses); discordant tropism (X4 in CSF samples and R5 in plasma)…”
Section: Potential Adjunctive Effect Of Maraviroc In the Cnsmentioning
confidence: 99%
“…The compound has been associated with some immunological benefits such as a higher CD4 increase and, although less than expected, reduced immune activation in patients with poor immunological recovery. [186] The drug, used in combination with other ARVs, has been proven to be effective in blocking HIV entry both in naïve and in experienced patients. The CNS target cells are usually expressing the CCR5 and most of the viruses are R5 tropic in the CSF (even if patients harbour X4-tropic viruses); discordant tropism (X4 in CSF samples and R5 in plasma)…”
Section: Potential Adjunctive Effect Of Maraviroc In the Cnsmentioning
confidence: 99%
“…Further, up to 30% of treated patients fail to recover peripheral CD4 þ [immunological nonresponders (INR)] [35], particularly those starting cART late in the course of disease, with severe CD4 þ depletion. This particular outcome has been associated with a high risk of clinical events and death [36][37][38] as well as poor response to experimental treatments [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…This increase might be due to the effect of intensification therapy, especially on the ongoing viral replication. Several clinical trials have argued on ART intensification, and the results were conflicting; no effects on the residual viremia measured by the single copy assay [20][21][22] or on immunological recovery [23] were reported. Some observational studies showed that at least 76% of HIV infected patients starting ART achieved an undetectable viral load within the first 6 months of therapy [24], while a percentage of 9%-45% did not obtain an appropriate recovery of CD4+ T cells count [25,26].…”
Section: Discussionmentioning
confidence: 99%